2021
DOI: 10.3892/ol.2021.13104
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of competitive endogenous RNAs networks reveals potential prognostic biomarkers associated with epithelial ovarian cancer

Abstract: Ovarian cancer (OC) is a major health threat to females, as it has high morbidity and mortality. Evidence has increasingly demonstrated that long non-coding RNAs (lncRNAs) regulate OC progression and they may have value as early diagnostic biomarkers, prognostic biomarkers and/or therapeutic targets. In the present study, the regulatory mechanisms and prognosis associated with cancer-specific lncRNAs and their related competing endogenous (ce)RNA network in OC were investigated. The differential expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Furthermore, the downregulation of VLDLR-AS1 was related to poor survival and appeared to be an oncogene in OC cellular function (21). In addition, Wu et al demonstrated that as a protective gene in OC development, the downregulation of VLDLR-AS1 was related to poor survival (22). In contrast to our findings, Takahashi et al revealed that VLDLR-AS1 was significantly upregulated in hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 91%
“…Furthermore, the downregulation of VLDLR-AS1 was related to poor survival and appeared to be an oncogene in OC cellular function (21). In addition, Wu et al demonstrated that as a protective gene in OC development, the downregulation of VLDLR-AS1 was related to poor survival (22). In contrast to our findings, Takahashi et al revealed that VLDLR-AS1 was significantly upregulated in hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 91%
“…According to Chen et al, high-expressed MIR3945HG levels were strongly connected with shorter survival of patients with LUSC 36 . Wu et al discovered that the LncRNA AC002467.1, which was found to be abnormally expressed in ovarian cancer, had a negative relationship with the survival of ovarian cancer patients 37 . AC008972.2 has been linked to m7G RNA methylation in colon cancer, according to Liu et al 38 .…”
Section: Discussionmentioning
confidence: 99%